A case study: evaluating the difference of technique by using efficiency index in elite male freestyle swimmers - Yang, H.; Xu, X.; Yu, W.; Huang, C.; Gao, B. (ISBS - Conference Proceedings Archive (Konstanz), 2005)
The purpose of the study was to evaluating the difference of technique by using efficiency index in elite male freestyle swimmers during their training periods. Two swimmers were selected to take a 6 x 50 m freestyle descend set in a 50 m swimming pool. The mean velocity (MV), stroke length (SL), stroke cycle (SC), efficiency index (El) and concentration of blood lactate (BL) were measured and compared to illuminate the difference of swimming technique and its impact on the performance level. According to previous and present studies, efficiency index is a useful measurement to evaluate the efficiency of the technique of swimmers. From limited number of subjects in the study, we speculated that the most effective intensity of improving efficiency of swimming technique is a little bit higher than anaerobic threshold.